2019
DOI: 10.1093/jnci/djz113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Validation of Breast Cancer Risk Prediction Models and Projections for Future Risk Stratification

Abstract: Background External validation of risk models is critical for risk-stratified breast cancer prevention. We used the Individualized Coherent Absolute Risk Estimation (iCARE) as a flexible tool for risk model development and comparative model validation and to make projections for population risk stratification. Methods Performance of two recently developed models, one based on the Breast and Prostate Cancer Cohort Consortium a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 65 publications
0
70
0
Order By: Relevance
“…First, UK Biobank participants tend to be healthier than the general population, and Color Genomics participants are likely to be enriched for genetic disease compared to the general population 35 . Within any target population, a comparison of predicted and observed disease rates can allow for recalibration of risk estimates, as recently performed for a breast cancer prediction tool 36 . Second, our analysis focused on the role of monogenic variants in the nine genes associated with the three CDC tier 1 genomic conditions; additional efforts are needed to include variants in other known or newly discovered genes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…First, UK Biobank participants tend to be healthier than the general population, and Color Genomics participants are likely to be enriched for genetic disease compared to the general population 35 . Within any target population, a comparison of predicted and observed disease rates can allow for recalibration of risk estimates, as recently performed for a breast cancer prediction tool 36 . Second, our analysis focused on the role of monogenic variants in the nine genes associated with the three CDC tier 1 genomic conditions; additional efforts are needed to include variants in other known or newly discovered genes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Given that breast cancer risk prediction models under-perform with regard to estimating individual risk, researchers have attempted to incorporate MPD into such models to improve their performance (as recently reviewed in Louro et al [2]). Multiple studies [2] have found that adding MPD to risk models improves breast cancer risk prediction, and efforts to incorporate MPD in newer risk models are ongoing [3,4]; however, to date, improvements in discriminatory accuracy have been modest.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, specific molecular subtypes, such as ER− breast cancers and the subset of ER− basal-like tumours, were more likely to be interval cancers. Predictive modelling of breast cancer has been proposed as a potential tool for personalised medicine and risk-stratified screening, [45][46][47] and future efforts might be used within screening programmes to improve the detection of more aggressive ER− breast cancers, particularly amongst those at higher risk of developing such cancers. With increased technologic advances in imaging modalities, it will be important to assess how these impact screen-detected tumours, and whether they can also improve detection for more aggressive ER-negative tumours that are more likely to be diagnosed outside of most screening programmes' age ranges.…”
Section: Discussionmentioning
confidence: 99%